Food and Energy Sovereignty as a Pancasila Economic Project: A Study of Soemitro's Book Djojohadikusumo Anti-colonialism - Anang Fahmi Luqmawan Putra; Yudhie Haryono (JURNAL ECONOMINA, 2026)
The documentary film “Pesta Babi” (Pig Feast) by Watchdoc, along with the accompanying narratives, has sparked a serious debate regarding the National Strategic Projects (PSN) in South Papua—specifically the food estate and bioethanol plantation projects. This article is not intended to silence legitimate criticism; indeed, criticism serves as a healthy vitamin for democracy. Rather, it aims to provide a comprehensive, constitutional, and value-based analytical framework for interpreting the Papua PSN policy through the lenses of "Soemitronomics" and Pancasila axiology. The central argument posits that the Papua PSN—provided it is implemented with proper governance, fairness, and respect for the constitutional rights of indigenous communities—represents a legitimate expression of national food and energy sovereignty. This constitutes a strategic imperative that Soemitro Djojohadikusumo had highlighted as early as the dawn of independence. Criticisms regarding implementation should be addressed through improved governance rather than the abandonment of the vision for sovereignty. Ultimately, the hope is that any development program will evolve to become increasingly effective and aligned with constitutional principles.